School administrators' use of collaborative autobiography as a vehicle for reflection on accountability pressures. Issue 4 (3rd July 2016) - Diehl, Julie N.; Gordon, Stephen P.
Abstract: This research studied accountability pressures faced by five school administrators, and explored collaborative autobiography as a way for administrators to reflect on and address those pressures. The administrators cycled back and forth between reflective writing and group dialogue as they contemplated accountability pressures, their life histories in relationship to the pressures, and their preferred future. The participants reported that the process helped them to better understand accountability pressures and develop strategies for negotiating those pressures.